2010
DOI: 10.1590/s0006-87052010000300021
|View full text |Cite
|
Sign up to set email alerts
|

Fungos micorrízicos arbusculares e rizobactérias promotoras de crescimento na aclimatização de zingiber spectabile

Abstract: RESUMOMicrorganismos benéficos exercem importantes funções para a sobrevivência e o desenvolvimento de plantas micropropagadas. O objetivo deste trabalho foi avaliar o potencial de fungos micorrízicos arbusculares (FMA) e rizobactérias promotores de crescimento de plantas (RPCP), isolados e/ou combinados (em dupla inoculação) na aclimatização de Zingiber spectabile Griff. O experimento foi realizado em casa de vegetação utilizando tubetes de 300 mL e pó da casca de coco (Amafibra ® ) como substrato. O delineam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
(5 reference statements)
1
3
0
6
Order By: Relevance
“…Similar results were also reported by Oliveira et al (2010) during the acclimatization of Z. spectabile, with the use of other substrates and inoculated with fungus arbuscular mycorrhizal fungi. Others species of Zingiberales (Etlingera elatior, Zingiber officinal, Heliconia velloziana) also presented great survival to acclimatization process (GIRARDI and PESCADOR, 2010;DAS et al, 2013;QUISEN et al, 2014;RODRIGUES et al, 2015).…”
Section: Acclimatizationsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were also reported by Oliveira et al (2010) during the acclimatization of Z. spectabile, with the use of other substrates and inoculated with fungus arbuscular mycorrhizal fungi. Others species of Zingiberales (Etlingera elatior, Zingiber officinal, Heliconia velloziana) also presented great survival to acclimatization process (GIRARDI and PESCADOR, 2010;DAS et al, 2013;QUISEN et al, 2014;RODRIGUES et al, 2015).…”
Section: Acclimatizationsupporting
confidence: 88%
“…However, there are not completed established protocol to in vitro Z. spectabile, just few studies in some steps of micropropagation of this species are available (FARIA and ILLG, 1995;OLIVEIRA et al, 2010;MOREIRA et al, 2012;NERY et al, 2015). In none of these studies were used seed to in vitro established and propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, Arthrobacter is a bene cial functional bacteria that can improve the IAA content and salt tolerance of plants (Velázquez-Becerra et al 2011). One of the important characteristics of the genus Bacillus is that it can produce spores with special resistance under adverse conditions, thus playing an active role in preventing plant diseases, improving plant resistance, and promoting plant growth (Oliveira et al 2010;Probanza et al 2002). Serratia is a bene cial bacteria that can tolerate heavy metals and repair plants, playing an important role in protecting the environment (76).…”
Section: Discussionmentioning
confidence: 99%
“…The acclimatization experiment of Camellia sinensis inoculated with Azospirillum showed changes in the shoot length and fresh weight after a period of 90 days (Thomas et al 2010). (Oliveira et al 2010) observed an increase in the shoot and fresh-root weight of Zingiber spectabile inoculated with Bacillus pumillus after three months. In trials with rootstocks of Prunus, plant height effects were observed after a period of between 90 and 150 days after inoculation (Bonaterra et al 2003).…”
Section: Discussionmentioning
confidence: 99%